PEMAHAMAN FILOSOF AL-FAROBI - Fuady, Siti Tsamrortul; Suhaebi, Ebi (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Al-Farobi was a Muslim philosopher who laid the foundations of Islamic philosophy sequentially and in detail, and then his philosophy was influenced by Greek philosophy. Al-Farobi said this form was created from the cause of the first form (Allah) which is found in many parts, which is called genesis, when philosophers used the power of reason to fulfill the truth while the prophets were filled with reason. Revelation was given to the people they chose. Farabi's political philosophy is similar to Plato's philosophy of idealism. Leaders are the first agents of society who are able to achieve happiness, just as the heart is in the body, other parts of the body also help create the desired happiness.